(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The Main objective of this project is to develop a power management system that will control the power flow and energy demand of an integrated renewable energy system with the focus on solar energy and wind energy. These storage systems are needed to provide high reliability and control systems are necessary for the stable and optimal operation of the whole system. The voltage and frequency of the line side converter are controlled with indirect vector control with droop characteristics. The setting of frequencies varies according to the battery energy level, which slows down when the battery is charged or discharged. The system can also work if the wind power source is not available. An Intelligent Power Management System (IPMS) is developed to handle various changes in power supply and power demand by managing erratic power and providing a suitable control algorithm for the whole system. In order to test various power supply and power demand using a power system. The performed simulations confirm the ability of the IPMS to satisfy the load at all times using solar and wind power (which are unsteady renewables), through the support of batteries